Goldston Syndrome - A Rare Case Report - Nagabhushan B M; Pavitra N Aralikatti; Vijayalaxmi Gagandeep (JCDR Research and Publications Pvt. Ltd., 2016)
Goldston syndrome is a condition where Dandy-Walker malformation of brain is associated with polycystic kidneys. Newborn on day one came to Neonatal Intensive Care Unit for evaluation of hydrocephalus. Fetal cranial ultrasound revealed deficient vermis with a posterior fossa cyst communicating with 4th ventricle suggestive of Dandy-Walker malformation. Ultrasound abdomen and pelvis showed echogenic enlarged kidneys containing small cysts. The diagnosis of Goldston syndrome was suggested. Dandy-Walker malformation was confirmed by MRI brain.